ANALISIS PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KINERJA PEGAWAI LAPAS KELAS IIB BIREUEN - Iqval Brian Hanafi; Raihan Iskandar; Rizka Sylvia (LPPM-UNIKI, 2025)
The study aimed to analyze job satisfaction related to compensation and the work environment and their impact on employee performance. Quantitative associative research was used, and path-wise data analysis was used. The study was conducted on 58 employees of Class IIB Bireuen Prison. The results showed that (1) compensation had a direct and indirect effect on job satisfaction, through the work environment variable, amounting to 34.4%. (2) compensation had a direct and indirect effect on job satisfaction, through the compensation variable, amounting to 46.17%. (3) Compensation and the work environment simultaneously contributed to job satisfaction, amounting to 81.2%. (4) Compensation had a direct and indirect impact on employee performance, amounting to 42.75%. The work environment had an impact of 49.83%. (5) The total effect of compensation and the work environment on employee performance, through the job satisfaction variable, was 18%. (6) The contribution of compensation and the work environment to employee performance was 71.2%